﻿Which factors influence spatio–temporal changes in the distribution of invasive and native species of genus Carassius? - Jakub Fedorčák; Peter Križek; Ján Koščo (Aquatic Invasions)
Within the genus Carassius Jarocki, 1822 , the crucian carp (C. carassius L., 1758) occurs naturally in the northern part of Middle Danube Basin (Austria, Morava, Slovakia). This species has the least concern status in this region, but observations in the last decades suggest that it is very close to extinction here. The distribution of crucian carp is limited to a small number of vanishing lentic habitats (oxbow lakes, marshlands). These biotopes are in the last stage of succession due to the drying up of the landscape and a reduction in the creation of new natural alluvial habitats. The non-native cyprinid, C. gibelio (Bloch, 1782), known as gibel carp and Prussian carp, has gradually become eudominant in a wide spectrum of habitats/biotopes since the 1960s Several biological adaptations of non-native species are generally considered the strong basis for the mass spreading in the invaded area. The other side of the expansion of non-native C. gibelio is affected by anthropic activities associated with fish farming, translocation and stocking the fish in open water ecosystems. In this study, we analysed historical scientific data on the distribution of Carassius spp. published from the 19th century to the present from the mentioned areas. The results suggest that the number of records of invasive C. gibelio has gradually increase in rivers, regulated channels and creeks, which could be considered as natural pathways of spreading. However, the presence of invasive C. gibelio in artificial biotopes (fishponds, reservoirs) is continuous from the 1960s. In the area mentioned, the artificial biotopes are managed by national fisheries associations and relate to the historical way of farming in Central and Eastern European countries. To show the current state of the fishing grounds of the Slovak Angling Association, we a created the distribution map based on the Carassius spp. catches recorded in last two decades.